Coprecipitation Method of Synthesis, Characterization, and Cytotoxicity of Pr3+:LaF3 (CPr = 3, 7, 12, 20, 30%) Nanoparticles - Maksim S. Pudovkin; Pavel V. Zelenikhin; Victoria Shtyreva; Oleg A. Morozov; Darya A. Koryakovtseva; Vitaly V. Pavlov; Yury N. Osin; Vladimir G. Evtugyn; Albert A. Akhmadeev; Alexey S. Nizamutdinov; Vadim V. Semashko (Journal of Nanotechnology)
The Pr3+:LaF3 (CPr = 3, 7, 12, 20, 30%) nanoparticles were characterized by means of high-resolution transmission electron microscopy, X-ray diffraction, optical spectroscopy, energy dispersive X-ray spectroscopy, dynamic light scattering, and MTT assay. It was revealed that the average diameter of all the NPs is around 14–18 nm. The hydrodynamic radius of the Pr3+:LaF3 (CPr = 7%) nanoparticles strongly depends on the medium. It was revealed that hydrodynamic radii of the Pr3+:LaF3 (CPr = 7%) nanoparticles in water, DMEM, and RPMI-1640 biological mediums were 18 ± 5, 41 ± 6, and 186 ± 8 nm, respectively. The Pr3+:LaF3 (CPr = 7%) nanoparticles were nontoxic at micromolar concentrations toward COLO-320 cell line. The lifetime curves were fitted biexponentially, and for the Pr3+:LaF3 (CPr = 7%) NPs, the luminescence lifetimes of Pr3+ ions were 480 ± 2 and 53 ± 5 nanosec.